Socio-cognitive correlates of intention to use Toombak: a cross-sectional study among students (13-16 years) in Khartoum State, Sudan - Hatim Mohammed Almahdi; Rouf Wahab Ali; Elwalid Fadul Nasir; Anne Nordrehaug Åstrøm (BMC, 2017)
Abstract Background Toombak is a form of smokeless tobacco, locally made and consumed in Sudan. It is associated with a number of health hazards, particularly oral cancer. This study was set out to assess the prevalence and socio-demographic distribution of its use, and to explore the socio-cognitive factors affecting the intention to use Toombak among secondary school students in Khartoum State, Sudan. Methods A cross-sectional school-based study was conducted in 2013-2014 where schools were randomly selected using a one-stage stratified sampling procedure. The sample size was calculated to consist of 1526 students. Data were collected through a self-administered questionnaire, which contained some cognitive constructs; information received, social image, attitudes, normative social influence, accessibility to Toombak, socio-demographics and Toombak use related variables. Results A total of 1670 secondary school students participated in the study. More than half of them 53.4% were <15-years-old and 53.6% were females. Only 5.3% of the students reported intention to use Toombak. Among the students 10.9% were ever Toombak users, 81.6% reported a positive attitude towards its use and 60.7% had received information about its harmful effects. A total of 72.6% reported normative social influence towards using Toombak and 62.5% perceived a negative social image attached to its use. Most of the students, 70.8% reported exposure to anti-Toombak information, 41.8% confirmed exposure to Toombak advertisement and 87.5% reported indirect access to its sale. Younger students reported ever use of Toombak less frequently than their older counterparts (38.4% versus 61.6%), p < 0.001. Males reported ever use of Toombak more frequently than did females (74.3% versus 25.7%), p < 0.001. According to the regression model, individuals who perceived a positive social image of Toombak users and had past experience were more likely to intend to its use. Conclusions The present study suggested that the prevalence of Toombak use among Sudanese secondary school students is low and that male and older students are more frequent users. Students' decision to use Toombak was based upon past experience with Toombak use and the social image attached to its use. Easy access to Toombak and encouragement from friends and classmates were among the factors which support intention to use Toombak but only in the unadjusted analyses.